Переклад непрямих мовленнєвих актів з німецької мови на українську - Пірог, Інна Іванівна; Сапко, Дмитро Олегович (Київський національний університет імені Тараса Шевченка)
The research in the field of indirect speech acts showed the necessity to provide more effective theoretical base for indirect speech acts and their translation. So the research opened some new possibilities for scientific work in the field of indirect speech acts and their translation devices. The contrastive analysis of the use of indirect speech acts in German and Ukrainian also showed a lot of differences.

Проведенное исследование открывает новые возможности дальнейших научных разработок в области классификаций косвенных речевых актов и способов их перевода. Сравнительный анализ использования косвенных речевых актов в немецком и украинском языках показал наличие большого количества несоответствий, что открывает возможности новых исследований.
Keywords: прагмалінгвістика; переклад; непрямий мовленнєвий акт; класифікація; прагмалингвистика; косвенный речевой акт; pragmalinguistics; indirect speech act